KAJIAN METODE PEMBELAJARAN BACA TULIS AL QUR’AN DALAM PERSPEKTIF MULTIPLE INTELLIGENCES - Abd. Gafur (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2013)
The study is intended to describe and analyze the learning method in reading and writing the Qur’an in the perspective of multiple intelligences theory. The study uses qualitative approach and is conducted through library research. Analysis process of the study follows the main steps such as: 1) collecting the references related to the learning method of reading and writing the Qur’an and multiple intelligences theory 2) reviewing the variety of the learning method in reading and writing the Qur’an 3) analyzing the learning method of reading and writing the Qur’an in the perspective of multiple intelligences 4) inferring the conclusion. The study gained some findings as follows: 1) the implementation of learning the Qur’an in the perspective of multiple intelligences proved that intelligence is already internalized into each variety of learning the Qur’an such as linguistic, mathematics, interpersonal, musical, spatial, kinesthetic, and intrapersonal intelligences 2) the study investigates three methods of learning the Qur’an such as Baghdadiyah, Qiroati, and Al-Barqy methods; and it can be inferred that Baghdadiyah method already implements the learning method of the Qur’an in line with the learning system and method of the Qur’an based on multiple intelligence, except naturalist intelligence. Al-Barqy method doesn't accommodate two aspects of intelligence: kinesthetic and naturalist intelligences. Whereas, Qiroati method only implements four aspects of intelligence such as linguistic, mathematics, spatial, and musical intelligences.